2016
DOI: 10.1111/ceo.12802
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced vascular endothelial growth factor secretion by retinal pigment epithelial cells is inhibited by melatonin via decreased accumulation of hypoxia‐inducible factors‐1α protein

Abstract: This study suggests that melatonin may have potential value in the prevention and treatment of various retinal diseases associated with increase of VEGF, vascular leakage and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Endothelial cells in the tumor microenvironment serve a pivotal role in the development and progression of cancer through modulating angiogenesis (8,45). Previous studies demonstrated that pharmacological concentrations of MLT have a direct anti-angiogenic effect though the suppression of proliferation in vascular endothelial cells, as well as an indirect effect via inhibition of pro-angiogenesis cytokines, including VEGF, epidermal growth factor and insulin-like growth factor (37,41,47). VEGF is one of the most potent pro-angiogenic cytokines, which specifically triggers the proliferation of endothelial cells and increases permeability (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells in the tumor microenvironment serve a pivotal role in the development and progression of cancer through modulating angiogenesis (8,45). Previous studies demonstrated that pharmacological concentrations of MLT have a direct anti-angiogenic effect though the suppression of proliferation in vascular endothelial cells, as well as an indirect effect via inhibition of pro-angiogenesis cytokines, including VEGF, epidermal growth factor and insulin-like growth factor (37,41,47). VEGF is one of the most potent pro-angiogenic cytokines, which specifically triggers the proliferation of endothelial cells and increases permeability (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism of MLT varies in different cancer types (36). Additionally, reports indicated that MLT decreases the expression of HIF-1α and VEGF caused by different factors in various cultivated cells, particularly hypoxia-induced accumulation of HIF-1α protein and expression of VEGF (37-39). Accumulating evidence indicates that the antitumor effect of MLT is associated with the inhibition of angiogenesis (24,40,41).…”
Section: Introductionmentioning
confidence: 99%
“…Similar HIF-1 inhibitory effects of melatonin were observed in other cancer models, including pancreatic ductal cells, cervical cancer, and lung cancer [ 61 ]. Melatonin was also effective through HIF-1 inhibition [ 62 ].…”
Section: Melatonin and Cancer Hallmarksmentioning
confidence: 99%
“…Melatonin has an inhibitory effect on HIF1 which in turn inhibit the altered metabolism of cancer. In the previous section (sustained proliferative signaling) the inhibition of HIF1 by melatonin was discussed [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Melatonin and Cancer Hallmarksmentioning
confidence: 99%
“…In vivo, tissue repair is induced by hypoxia-inducible factor 1α (HIF-1α) (Semenza, 2012). The downstream factors such as stromal cell-derived factor (SDF-1α) (Krieger et al, 2016), vascular endothelial growth factor (VEGF) (Lin et al, 2012), platelet-derived growth factor b (PDGF-b) (Lai et al, 2017;Vanden Berg-Foels, 2013) and macrophage chemotactic protein-1 (MCP-1) (Artlett, 2013) recruit several cell types to participate in remodeling process (Shirozu et al, 1995;Xu et al, 2013). The mechanism of tissue repair makes in situ regeneration feasible.…”
mentioning
confidence: 99%